2017
DOI: 10.1002/etc.3778
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and behavioral impacts of diesel and fuel oil on the Antarctic amphipod Paramoera walkeri

Abstract: Toxicity testing with Antarctic species is required for risk assessment of fuel spills in Antarctic coastal waters. The lethal and sublethal (movement behavior) sensitivities of adults and juveniles of the Antarctic amphipod Paramoera walkeri to the water accommodated fractions (WAFs) of 3 fuels were estimated in extended-duration tests at -1 °C to 21 d. Response of P. walkeri for lethal hydrocarbon concentrations was slow, with 50% lethal concentrations (LC50s) first able to be estimated at 7 d for adults exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
(135 reference statements)
0
13
0
Order By: Relevance
“…A test duration of 10 d has previously been used in tests with Antarctic and subantarctic species (e.g., Payne et al ; Marcus Zamora et al ; Holan et al , , ), and provides a good compromise between the shortest duration required to consistently see a response, and the extended duration that is appropriate for cold‐climate species with slow metabolic rates. For some cold‐climate species, even longer test durations (up to 4 wk) have been used (e.g., Sfiligoj et al ; Brown et al ) and may have provided more sensitive results, but, to be in keeping with the premise of the rapid method, these durations were impractical and beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 99%
“…A test duration of 10 d has previously been used in tests with Antarctic and subantarctic species (e.g., Payne et al ; Marcus Zamora et al ; Holan et al , , ), and provides a good compromise between the shortest duration required to consistently see a response, and the extended duration that is appropriate for cold‐climate species with slow metabolic rates. For some cold‐climate species, even longer test durations (up to 4 wk) have been used (e.g., Sfiligoj et al ; Brown et al ) and may have provided more sensitive results, but, to be in keeping with the premise of the rapid method, these durations were impractical and beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 99%
“…For the embryonic and larval toxicity tests that were done in open vials, the exposure concentrations of total hydrocarbon content in WAFs were modeled from the measured concentrations in the WAF depletion tests (Brown et al 2016). Exposure concentrations used to model sensitivity estimates were derived by calculating the time‐weighted mean total hydrocarbon content between pairs of successive measurements in the 100% WAFs and dilutions (Brown et al 2017), to give overall exposure concentrations for each time point (Tsvetnenko and Evans 2002; Organisation for Economic Co‐operation and Development 2019). These modeled concentrations integrated the loss of hydrocarbons over time, and renewal of test solutions at 4‐d intervals.…”
Section: Methodsmentioning
confidence: 99%
“…There are few published studies on the sensitivity of Antarctic marine invertebrates to fuels. Amphipods, copepods, echinoderms, and the coastal Antarctic zooplankton community have been demonstrated to be sensitive to SAB diesel and fuel oils at low concentrations (Lane and Riddle 2004; Payne et al 2014; Alexander et al 2017; Brown et al 2017). Most of these studies however, have examined a single species or life stage, and a single fuel only.…”
Section: Introductionmentioning
confidence: 99%
“…Former waste disposal sites on shorelines around coastal research stations, combined with meltwater runoff through such sites, has also resulted in pollution of marine sediments by metals, persistent organic pollutants and hydrocarbons, leading to localized changes in macrofaunal communities (Lenihan and Oliver, 1995;Stark et al, 2005Stark et al, , 2014, uptake of contaminants by biota and reduced biodiversity (Duquesne and Riddle, 2002;Stark et al, 2004). At a species level there is relatively limited knowledge on the sensitivity and bioaccumulation of pollutants on benthic species (Lister et al, 2015;Alexander et al, 2017;Brown et al, 2017). Heavy-metal studies have shown demonstrated variability within phyla and further research is required before water quality guidelines for the Southern Ocean can be established (Kefford et al, 2019;Webb et al, 2019).…”
Section: Pollution Responsesmentioning
confidence: 99%